2012
DOI: 10.1186/1743-7075-9-112
|View full text |Cite
|
Sign up to set email alerts
|

Jerusalem artichoke and chungkookjang additively improve insulin secretion and sensitivity in diabetic rats

Abstract: Jerusalem artichoke (Helianthus tuberosus Linne, HTL) and chungkookjang (CKJ; fermented soybeans) both modulate energy and glucose metabolism. However, the mechanism and their additive effects are unknown. We investigated whether the consumption of HTL and CKJ altered insulin sensitivity, insulin secretion capacity and β-cell survival in type 2 diabetic animals. Rats were divided into partially pancreatectomized (Px) diabetic rats, and sham operated non-diabetic control rats and all fed high fat diets. Diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Also, Jerusalem artichoke decrease fasting serum glucose levels perhaps due to it is rich in fructan and coumarins [ 13 22 ]. Jerusalem artichoke had anti-diabetic effects due to high in fructoligossacharides that may decrease insulin resistance by mechanisms that remain unknown [ 23 ]. Therefore, the degree of polymerization of fructan is considered as a factor that influences hyperglycemia amelioration and α-glucosidase inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Jerusalem artichoke decrease fasting serum glucose levels perhaps due to it is rich in fructan and coumarins [ 13 22 ]. Jerusalem artichoke had anti-diabetic effects due to high in fructoligossacharides that may decrease insulin resistance by mechanisms that remain unknown [ 23 ]. Therefore, the degree of polymerization of fructan is considered as a factor that influences hyperglycemia amelioration and α-glucosidase inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to TPB, chungkookjang (CKJ; fermented soybeans) has also been considered to modulate energy and glucose metabolism. Yang et al [41] evaluated an anti-diabetic effects of TPB and CKJ supplementary diet in diabetic rats. Animals were divided into four experimental groups (diabetic-control, CKJ, CKJ+TPB, and TPB).…”
Section: Tpb Studies In Animal Experimentsmentioning
confidence: 99%
“…Administration of the ethanol extract of H. tuberosus tuber exhibited an inhibitory effect (24.5 %) on diabetic rat kidney tissue thiobarbituric acid reactive substance (TBARS) levels but did not restore GSH (reduced glutathione) levels in the kidney, liver and heart tissues of diabetic rats (Aslan et al 2010 ). Studies by Yang et al ( 2012 ) reported that Jerusalem artichoke and chungkookjang (fermented soybeans) enhanced glucose tolerance in different manners and exhibited partially additive and complementary effects by reversing insulin resistance and enhancing β-cell function in diabetic rats. The combined treatment reduced visceral fat without modulating energy intake compared to the diabetic control.…”
Section: Antidiabetic and Hypolipidaemic Activitiesmentioning
confidence: 98%